Advanced portal venous access techniques for transjugular intrahepatic portosystemic shunt placement. Issue 1 (24th December 2021) - Partovi, Sasan; Li, Xin; Shwaiki, Omar; Rashwan, Basem; Ruff, Christer; Grozinger, Gerd; Gadani, Sameer; Szaflarski, Diane; Thompson, Dustin; D'Amico, Guiseppe; Levitin, Abraham; Kapoor, Baljendra
Abstract : Introduction: Transjugular intrahepatic portosystemic shunt (TIPS) placement is a well-established but technically challenging procedure for the management of sequelae of end-stage liver disease. Performed essentially blindly, traditional fluoroscopically guided TIPS placement requires multiple needle passes and prolonged radiation exposure to achieve successful portal venous access, thus increasing procedure time and the risk of periprocedural complications. Several advanced image-guided portal access techniques, including intracardiac echocardiography (ICE)-guided access, cone-beam CT (CBCT)-guided access and wire-targeting access techniques, can serve as alternatives to traditional CO2 portography-based TIPS creation. Methods: A literature search was performed on the electronic databases including MEDLINE and Embase, from 2000 to the present to identify all relevant studies. The reference list also included studies identified manually, and studies referenced for other purposes. Findings: The main benefit of these advanced access techniques is that they allow the operator to avoid essentially blind portal punctures, and the ability to visualise the target, thus reducing the number of required needle passes. Research has shown that ICE-guided access can decrease the radiation exposure, procedure time and complication rate in patients undergoing TIPS placement. This technique is particularly useful in patients with challenging portal venous anatomy. However, ICE-guided access requires additional equipment and possibly a second operator. Other studies have shown that CBCT-guided access, when compared with traditional fluoroscopy-guided access, provides superior visualisation of the anatomy with similar amount of radiation exposure and procedure time. The wire-targeting technique, on the other hand, appears to offer reductions in procedure time and radiation exposure by enabling real-time guidance. However, this technique necessitates percutaneous injury to the liver parenchyma in order to place the target wire. Conclusion: Advanced portal access techniques have certain advantages over the traditional fluoroscopically guided TIPS access. To date, few studies have compared these advanced guided access options, and further research is required.